E-Government Based Urban Governance on the Smart City Program in Makassar, Indonesia - Rudi Hardi; Srirath Gohwong (Journal of Contemporary Governance and Public Policy, 2020)
This article discusses about urban governance of Smart City Program in the Makassar City, which is the mainstay program of the Makassar City Government and identifies factors that are driving and inhibiting the realization of Good Urban Governance based on E-Government in Smart City Program. This type of research was qualitative with a descriptive approach. Data collecting was used instrument in the form of observation and documentation then developed from the interviews of informants. The fact in the field indicated that E-Government-based urban governance on Smart City program in the Makassar is seen from the indicators of urban management, namely planning, organizing, implementing and controlling according to the development goals in the Makassar Government's vision and mission.